Empirical essays on export composition and behaviour in a developing country context - Hazel, Selvon (2014)
There is a growing recognition that the composition and behaviour of exports matter for development. However, empirical studies examining these issues focus primarily on develop countries and larger emerging economies. We therefore seek to fill a gap in the literature by examining the extent and the factors explaining export specialization, the dynamics of export growth and the duration of export relationships from the perspective of a small developing country, Trinidad and Tobago, for the period, 1996-2009. These issues are particularly important for trade policy formulation and export promotion. To examine the factors explaining export specialization, we use HS 4-digit export data and conduct our estimation using mainly Fractional Logit Generalized Linear Model (GLM). To explore the factors explaining the dynamics of export growth, we use HS 6-digit manufacturing export data and estimate our model using Ordinary Least Squares (OLS) and Poisson Pseudo-Maximum Likelihood Estimation (PPML). Finally, to explain to factors influencing export duration, we also use HS 6-digit manufacturing export data and employ Stratified Cox Estimation.